El texto narrativo en la clínica psicoanalítica del síntoma de aprendizaje del lenguaje: un análisis estructural (2011)
This article presents data of one of the studies developed in the thesis "The narrative text as therapeutic intervention in written language problems in adolescence" (Grohs, 2009): a structural analysis of the narrative text produced in psychoanalytical psychotherapy. This analysis points to the possibility of using the narrative text as an instrument of intervention and of measuring results in research in clinic psychotherapy of adolescents who present symptoms in written language learning.